Efficacy and Safety of Ruxolitinib in Turkish Patients with Chronic Myeloproliferative Neoplasms: A Multicenter and Retrospective Analysis - Soyer, N.; Turgut, M.; Haznedaroglu, I.; Yilmaz, F.; Aydogdu, I.; Pir, A.; Yavasoglu, I. (Pergamon-Elsevier Science Ltd, 2017)
…
8th International Eurasian Hematology Oncology Congress (EHOC) -- OCT 18-21, 2017 -- Istanbul, TURKEY